Job crafting and employee commitment: key drivers for retaining skilled talent in digitally transformed organizations - Richard Kofi Boateng; Salomey Ofori Appiah (Future Business Journal)
Abstract This study investigates the relationship between job crafting and staff retention at Ghana's Environmental Protection Agency, with employee commitment as a mediator. Drawing on Social Exchange theory, the study used a quantitative approach, an explanatory design, and a simple random sampling technique to select 310 full-time employees across 11 branches of the Environmental Protection Agency in Ghana. The study employed Partial Least Squares Structural Equation Modeling to analyze the data. The results revealed that task crafting and cognitive crafting had a negative and insignificant effect on retention. Additionally, it was found that relational crafting significantly affects retention. Furthermore, the study found that commitment has a significant full mediating effect on the relationship between task crafting and retention. Commitment also fully mediated the link between cognitive crafting and retention; however, it partially mediated the link between relational crafting and retention. The researchers recommend that organizations invest in fostering relational and cognitive crafting, align task crafting with organizational goals, and strengthen commitment to improve retention. Moreover, stakeholders, including policymakers and HR professionals, should promote job crafting as a strategic tool while ensuring it is well-supported and aligned with organizational values. This study contributes to the literature on employee retention by applying social exchange theory and emphasizing the importance of commitment as a mediator.